ClC-1 chloride channels: state-of-the-art research and future challenges - Imbrici, Paola; Altamura, Concetta; Pessia, Mauro; Mantegazza, Renato; Desaphy, Jean-François; Camerino, Diana Conte (Frontiers in Cellular Neuroscience, 2015)
The voltage-dependent ClC-1 chloride channel belongs to the CLC channel/transporter family. It is a homodimer comprising two individual pores which can operate independently or simultaneously according to two gating modes, the fast and the slow gate of the channel. ClC-1 is preferentially expressed in the skeletal muscle fibers where the presence of an efficient Cl- homeostasis is crucial for the correct membrane repolarization and propagation of action potential. As a consequence, mutations in the CLCN1 gene cause dominant and recessive forms of Myotonia Congenita, a rare skeletal muscle channelopathy caused by abnormal membrane excitation, and clinically characterized by muscle stiffness and various degrees of transitory weakness. Elucidation of the mechanistic link between the genetic defects and the disease pathogenesis is still incomplete and, at this time, there is no specific treatment for Myotonia Congenita. Still controversial is the subcellular localization pattern of ClC-1 channels in skeletal muscle as well as its modulation by some intracellular factors. The expression of ClC-1 in other tissues such as in brain and heart and the possible assembly of ClC-1/ClC-2 heterodimers further expand the physiological properties of ClC-1 and its involvement in diseases. A recent de novo CLCN1 truncation mutation in a patient with generalized epilepsy indeed postulates an unexpected role of this channel in the control of neuronal network excitability. This review summarizes the most relevant and state-of-the-art research on ClC-1 chloride channels physiology and associated diseases.